Properties of plasmonic arrays produced by pulsed-laser nanostructuring of thin Au films - Grochowska, Katarzyna; Siuzdak, Katarzyna; Atanasov, Peter A.; Bittencourt, Carla; Dikovska, Anna; Nedyalkov, Nikolay N.; Śliwiński, Gerard (Beilstein Journal of Nanotechnology, 2014)
A brief description of research advances in the area of short-pulse-laser nanostructuring of thin Au films is followed by examples of experimental data and a discussion of our results on the characterization of structural and optical properties of gold nanostructures. These consist of partially spherical or spheroidal nanoparticles (NPs) which have a size distribution (80 ± 42 nm) and self-organization characterized by a short-distance order (length scale ≈140 nm). For the NP shapes produced, an observably broader tuning range (of about 150 nm) of the surface plasmon resonance (SPR) band is obtained by renewal thin film deposition and laser annealing of the NP array. Despite the broadened SPR bands, which indicate damping confirmed by short dephasing times not exceeding 4 fs, the self-organized Au NP structures reveal quite a strong enhancement of the optical signal. This was consistent with the near-field modeling and micro-Raman measurements as well as a test of the electrochemical sensing capability.
Keywords: Au nanostructures; laser dewetting; laser nanostructuring; plasmonic enhancement; self-organization